Jaap Sahib and Its Musicology: Exploring the Musicological Aspects of Jaap Sahib (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Jaap Sahib, one of the five Banis’ (texts) recited during Amrit Sanchaar (baptization ceremony in Sikh religion) and also included in Nitnem (daily routine of a Sikh) has its importance in other fields of knowledge, especially literature and Music. The research paper deals with the musicological aspect of the sacred text. The research covers study of musical terminology used in the text, taal (Indian music) discipline, Chhand (metre) discipline, Alankaar (literature) discipline, Dhyan Chitra (Indian music), Rasa (emotion) expression and linguistic aesthetics of the text to find the extent to which the modern musicology dwells in the text.